Evidence for Itinerant Carriers in an Anisotropic Narrow-Gap Semiconductor by Angle-Resolved Photoemission Spectroscopy - Ju, Sailong (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.